Diagnostic Possibilities of Standard Automatic and FunctionSpecific Perimetry (HFA, Octopus) in the Study of the Visual Field in Patients with Compression in the Chiasm-Sellar Region - N. A. Gavrilova; E. E. Ioyleva; N. S. Gadzhieva; O. E. Tishchenko; N. Yu. Kutrovskaya; A. V. Zinov’eva (Oftalʹmologiâ, 2020)
The literature review presents the results of a static perimetry for the study of the visual field in patients with compression in the chiasm-sellar region on the Humphrey Visual Field Analyzer (HFA) and Octopus. These models of perimeters are recognized as the “gold standard” and are most widely used in the global ophthalmic practice. The analysis of research results using traditional and function-specific perimetry with selective stimulation of the magnocellular and koniocellular (frequency-doubling technology perimetry, FDT; short-wavelength automated perimetry, SWAP) visual pathways was performed. The literature data analysis allows us to conclude that the static perimetry for the study of the visual field in patients with chiasmatic compression is carried out quite widely and is informative. But despite this, there are no generally accepted recommendations on the use of certain testing strategies and programs for the diagnosis and further dynamic observation of changes in the visual field in patients with this pathology. In this regard, it is advisable to conduct further studies that will allow the formation of standard perimetric protocols for diagnosing and monitoring visual field defects in patients with compression in the chiasm-sellar region based on a comparative analysis of the diagnostic informativity of various strategies and programs.